The Causes and Prevention of Corporate Bond Default/The Nature and Extent of Losses to Bondholders in Corporate Reorganisation and Liquidation (Book). - Kincaid, E. A. (The Accounting Review, 1938)
Reviews two books "The Causes and Prevention of Corporate Bond Default," by David B. Jeremiah and "The Nature and Extent of Losses to Bondholders in Corporate Reorganization and Liquidation," by WiIliam E. Warrington.